PENERAPAN PERMAINAN ULAR TANGGA TERHADAP PHBS (PERILAKU HIDUP BERSIH DAN SEHAT) PADA SISWATUNAGRAHITA RINGAN DI SDLB IDAYU 1 MALANG - Hasanah, Khaeratul; Chusna, Mega Putriatul; Putri, Nadia Ayu Amalia; Andriani, Yulika; Novianti, Ranti; Ediyanto, E. (INOPENDAS: Jurnal Ilmiah Kependidikan, 2025)
This study aims to apply the snakes and ladders game media that can overcome the lack of PHBS (Clean and Healthy Living Behavior) skills, especially washing hands with soap and sorting waste in mild mentally retarded students at SLB Idayu 1 Malang. This research method uses experimental research with a one group pretest-posttest design, namely (1) pretest (2) treatment (3) posttest. Data were collected through the results of the pretest and posttest. The data analysis technique used a hypothesis test, namely the Wilcoxon test. The results concluded that there was an average value of all mentally retarded students in the pretest and posttest of 49.00 and 89.00. Thus, it can be said that the snakes and ladders game media has an effect on increasing PHBS skills in mild mentally retarded students at SLB Idayu 1 Malang.